New Regulation on Membership and Investor Shares in Credit Unions. Comparative Interpretation of Polish Law on Credit Unions - Bierecki, Dominik (Review of European and Comparative Law, 2024)
This paper analyses the 2023 amendment to the Act on Credit Unions of 9 November 2009 using dogmatic and comparative methods. First, the author considers membership of partnerships in credit unions in the context of the requirement of a common bond for membership. Second, the author analyses the legal status of investor shares, conditions of dividend payment on their basis, as well as their termination. In conclusion, the author indicates that Polish regulation on membership of partnerships requires establishing multiple common bond credit unions and that restrictions for holders of investor shares in credit unions are similar in Poland and the UK.